The Concept of Religious Tolerance in Reconstruction and Reinterpretation of Al-Kafirun by Mun'im Sirry (Critical Discourse Analysis of Teun A. Van Dijk) - Anam, Haikal Fadhil; Ghozali, Mahbub (JURNAL INDO-ISLAMIKA, 2022)
This research aims to explain the concept of religious tolerance of Mun'im Sirry from the reconstruction and reinterpretation of Sura al-Kafirun. This is library research using qualitative method and descriptive-explanatory research design. The analysis employed in this research is Critical Discourse Analysis by Teun A. Van Dijk. The authors use Critical Discourse Analysis to reveal the various strategic interests behind the writing of Sirry‘s commentary and the struggles of social and understanding of groups. The result of this research explains that the concept of religious tolerance offered by Sirry does not only stop in sociological framework, but, more than that, it also extends tolerance in a theological framework. In Sirry's perspective, Muslims need not only to respect, appreciate, acknowledge differences in belief with followers of other religions and live in harmony (sociological field), they also need to acknowledge the recognition of the possible salvation of other religious followers in the hereafter (theological field). Furthermore, the discourse cannot be separated from the power of the West as the controller of science and the ideologies that influence the discourse are rationalism, empiricism, or neo-mu‘tazilism.